Irupsi Generasi Beriman Digital Z dan Disrupsi Katekese Kebangsaan - Andalas, Mutiara (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2022)
This paper discusses the irruption of the digital faithful generation of Z in the Indonesian Catholic church and its disruption to citizenship catechesis. The discussion of citizenship catechesis will fall short if we still fixate on the classic definitions of catechesis, the method of catechesis, and the profile of catechists in the apostolic exhortation Cateceshi Tradendae (1979). The predigital world conditions ideas about them. An in-depth discourse on citizenship catechesis needs to depart from the digital faithful generation of Z irrupting in the Indonesian Catholic Church. 'Irruption', according to the liberation theologian Gustavo Gutiérrez, refers to the presence of people who previously lived at the underside of history. Previously being absented, they transform into the subject of history. Irruption is also an ecclesial process. The generation of Z has emerged in the history of the Indonesian Catholic church as homo religiosus digitalis. They bring the disruptive spirit of the digital era to the body of the Catholic church. As digital integrators, they are open to incorporating faith in their lives. Based on their autobiography, homo religiosus digitalis Z lives a connective pedagogy with distinctive characteristics from predigital believers. Their irruption shakes the identity of the catechist and their vocation to "teach the lesson of the faith" to today's disciples of Christ. The irruption of Z's digital faithful generation encourages the further exploration of new methods for citizenship catechesis in the contemporary Indonesian context. Abstrak Tulisan ini mendiskusikan irupsi generasi beriman Z dalam Gereja Katolik Indonesia yang disruptif terhadap katekese kebangsaan. Diskusi tentang katekese kebangsaan tak akan beranjak jauh jika kita masih terpaku pada definisi klasik katekese, metode berkatekese, dan profill katekis dalam seruan apostolik Cateceshi Tradendae (1979). Seruan apostolik ini dikondisikan oleh dunia pradigital. Diskursus mendalam tentang katekese kebangsaan perlu berangkat dari irupsi generasi Z. Istilah "irupsi", menurut teolog pembebasan G. Gutiérrez, menunjuk pada penyeruakan orang-orang yang sebelumnya hidup di sisi bawah sejarah. Mereka bertransformasi dari yang semula diabsenkan keberadaannya, kini menjadi subjek sejarah. Irupsi juga merupakan proses eklesial. Generasi Z menyeruak dalam panggung sejarah gereja Katolik Indonesia sebagai homo religiosus digital. Mereka membawa roh disruptif era digital. Meminjam kosakata Mark McCrindle tentang generasi Z sebagai “digital integrator”, insan digital Z terbuka untuk menginkorporasikan iman dalam kehidupan mereka. Berdasarkan autobiografi mereka, homo religiosus digital Z menghidupi pedagogi konektif yang karakteristiknya berbeda dari insan beriman pradigital. Irupsi mereka menggegarkan identitas katekis serta panggilannya untuk “mengajarkan pelajaran iman” kepada murid-murid Kristus pada masa kini.Irupsi insan beriman digital Z mendorong eksplorasi metode-metode baru untuk katekese kebangsaan dalam konteks Indonesia zaman now.